Aluminium-Nitride Thin-Films On Polymer Substrates Obtained by Adhesive Bonding. (3rd June 2021) - Azrak, Edy; Michaud, Laurent G.; Reinhardt, Alexandre; Tardif, Samuel; Bousquet, Marie; Vaxelaire, Nicolas; Eymery, Joël; Fournel, Frank; Montmeat, Pierre
Abstract : A scalable manufacturing method is demonstrated for the transfer of crystalline AlN thin-films deposited on 200 mm Si wafer onto a flexible and stretchable polymer. The resulting AlN-On-Polymer (AOP) can be bent and stretched. This novel transfer process allows a straightforward strain-engineering method of semiconductor thin-films when transferred onto polymer. Straining controllably semiconductor thin-films may alter their properties, which may boost the performance of the corresponding devices; e.g. the piezoelectric properties of AlN are enhanced upon tensile strain. We present here the transfer process of AlN thin-films onto polymer substrates; we discuss the influence of uniaxial strain on microstructural properties of AOP after in situ Raman spectroscopy assessments and relative strain evaluations by X-ray diffractions of AlN thin-films embedded in different types of stack configurations.